Swear Words Used by Japanese: A Descriptive Qualitative Study - Ariantari, Pande Kadek Dea; Budasi, I Gede; Ramendra, Dewa Putu (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study explores the use of swear words in the Japanese language, focusing on their forms, references, and communicative functions. The aim is to identify the types of swear words used by native speakers, analyze their morphological structures, and understand the meanings and roles they play in social interaction. A descriptive qualitative approach was used, employing interviews and document analysis as primary data collection methods. Instruments included the researcher as the key instrument, supported by document analysis sheets and interview guides. Data were collected from three native Japanese speakers, supplemented with related texts and online sources. The study identified 41 Japanese swear words categorized into 14 monomorphemic words, 17 polymorphemic words, 13 phrases, and 6 clauses. The references of these words varied, including sex (4), excrement (4), animals (4), mental illness (2), and death (3). Functionally, the swear words were used to express emotions (15), show aggression (12), deliver insults (20), emphasize a point (1), and establish group identity or solidarity (3). The findings reveal the complexity of swearing in Japanese, showing that such expressions play an important role in emotional release, group belonging, and social confrontation. This study enhances the understanding of Japanese sociolinguistics and pragmatics.